2019
DOI: 10.3762/bjnano.10.181
|View full text |Cite
|
Sign up to set email alerts
|

Engineered superparamagnetic iron oxide nanoparticles (SPIONs) for dual-modality imaging of intracranial glioblastoma via EGFRvIII targeting

Abstract: In this work, a peptide-modified, biodegradable, nontoxic, brain-tumor-targeting nanoprobe based on superparamagnetic iron oxide nanoparticles (SPIONs) (which have been commonly used as T 2-weighted magnetic resonance (MR) contrast agents) was successfully synthesized and applied for accurate molecular MR imaging and sensitive optical imaging. PEPHC1, a short peptide which can specifically bind to epidermal growth factor receptor variant III (EGFRvIII) that is overexpressed in glioblastoma, was conjugated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…[71] Some studies designed dual-modality nanoprobes for both MRI and fluorescence imaging of cancer cells and tumors. In this regard, Liu et al [72] designed a brain-tumor-targeting nanoprobe using Cy7.5-labeled PEGylated SPION nanoparticles modified with an EGFRvIII-targeting peptide (PEPHC1 peptide; sequence: HFLIIGFMRRAACGA) for dual-modality imaging (MRI and fluorescence imaging) of glioblastoma. Both in vitro and in vivo MR and fluorescence imaging demonstrated that the synthesized nanoprobe effectively targeted glioblastoma tumors in a U87MG-EGFRvIII xenograft mouse model.…”
Section: Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%
See 1 more Smart Citation
“…[71] Some studies designed dual-modality nanoprobes for both MRI and fluorescence imaging of cancer cells and tumors. In this regard, Liu et al [72] designed a brain-tumor-targeting nanoprobe using Cy7.5-labeled PEGylated SPION nanoparticles modified with an EGFRvIII-targeting peptide (PEPHC1 peptide; sequence: HFLIIGFMRRAACGA) for dual-modality imaging (MRI and fluorescence imaging) of glioblastoma. Both in vitro and in vivo MR and fluorescence imaging demonstrated that the synthesized nanoprobe effectively targeted glioblastoma tumors in a U87MG-EGFRvIII xenograft mouse model.…”
Section: Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%
“…Both in vitro and in vivo MR and fluorescence imaging demonstrated that the synthesized nanoprobe effectively targeted glioblastoma tumors in a U87MG-EGFRvIII xenograft mouse model. [72] In another study, Ye et al [73] employed GE11-functionalized lanthanidedoped magnetic and fluorescent upconversion nanoparticles (UCNPs) for the detection of triple-negative breast cancer (TNBC) cells using dual MRI and fluorescence imaging. The NaGdF 4 :Yb 3 + , Er 3 + @NaGdF 4 nanoparticles were modified with polyacrylic acid (PAA), and then coupled with GE11 peptide using EDC and N-hydroxysuccinimide (NHS) for EGFR targeting.…”
Section: Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%
“…PEPHC1 peptide was attached to SPIONs to target EGFRvIII in GBM. Nanostructures were found to be biodegradable, non-toxic and tunable for tumor imaging [195]. The boundary between normal cells and glioma cells is very difficult to differentiate precisely.…”
Section: Multimodal Imaging With Nanomaterialsmentioning
confidence: 99%
“…In this study, first, U87 MG and two weeks later SPIONs were injected into mice. They found that brain tumour MR imaging signal was strong, and the fluorescence image of the major fluorescence intensity in the brains of the mice that received the substance showed higher than the control mice [ 84 ].…”
Section: Nanoparticles In Multi‐modal Imagingmentioning
confidence: 99%